2007
DOI: 10.1128/aac.00186-07
|View full text |Cite
|
Sign up to set email alerts
|

Pyrophosphorolytic Excision of Nonobligate Chain Terminators by Hepatitis C Virus NS5B Polymerase

Abstract: Nonobligate chain terminators, such as 2-C-methylated nucleotides, block RNA synthesis by the RNAdependent RNA polymerase (RdRp) of hepatitis C virus (HCV). Previous studies with related viral polymerases have shown that classical chain terminators lacking the 3-hydroxyl group can be excised in the presence of pyrophosphate (PP i ), which is detrimental to the inhibitory activity of these compounds. Here we demonstrate that the HCV RdRp enzyme is capable of removing both obligate and clinically relevant nonobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 46 publications
3
46
0
Order By: Relevance
“…No pyrophosphorolysis could be observed in our experimental system with either WT or S282T NS5B, probably because of specific template requirements for this particular mechanism (14). Nevertheless, it was shown that S282T NS5B is able to excise chain-terminator analogues to the same extent as WT NS5B (14). Therefore, S282T mutant-mediated re- Tables 1 and 3 for comparative incorporation during initiation and from Tables 2 and 4 sistance to 2Ј-C-Me-NTP is only due to K m -based discrimination (Table 2).…”
Section: Vol 50 2006 Hcv Ns5b Resistance Toward 2ј-modified Analogumentioning
confidence: 97%
See 1 more Smart Citation
“…No pyrophosphorolysis could be observed in our experimental system with either WT or S282T NS5B, probably because of specific template requirements for this particular mechanism (14). Nevertheless, it was shown that S282T NS5B is able to excise chain-terminator analogues to the same extent as WT NS5B (14). Therefore, S282T mutant-mediated re- Tables 1 and 3 for comparative incorporation during initiation and from Tables 2 and 4 sistance to 2Ј-C-Me-NTP is only due to K m -based discrimination (Table 2).…”
Section: Vol 50 2006 Hcv Ns5b Resistance Toward 2ј-modified Analogumentioning
confidence: 97%
“…It was recently reported that HCV and bovine viral diarrhea virus polymerase resistance to nucleotide analogues could also be the result of pyrophosphorolysis leading to the excision of the analogue after its incorporation into the nascent RNA (10,14). No pyrophosphorolysis could be observed in our experimental system with either WT or S282T NS5B, probably because of specific template requirements for this particular mechanism (14). Nevertheless, it was shown that S282T NS5B is able to excise chain-terminator analogues to the same extent as WT NS5B (14).…”
Section: Vol 50 2006 Hcv Ns5b Resistance Toward 2ј-modified Analogumentioning
confidence: 99%
“…The coding sequence for HCV NS5B (genotype 1b, BK strain) was cloned into the bacterial expression vector pet21b. The hydrophobic region at the C terminus was removed (⌬21), and a hexa-histidine tag was introduced to facilitate protein purification (20,36). Mutant enzymes were generated via site-directed mutagenesis using the Stratagene QuikChange kit according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…The antiviral activity of 5-fluorocytidine against RNA and DNA viruses has been previously reported (29), as has the anti-HIV-1 activity of the reduced form of 5-fluorocytidine, 2=-deoxy-5-fluorocytidine (30), and that of the derivative 2=,3=-dideoxy-beta-L-5-fluorocytidine (30). Previous reports have demonstrated the antiviral activity of 2=-C-methylcytidine as a delayed chain terminator against RNA viruses, such as hepatitis C virus (HCV) and footand-mouth disease virus (FMDV) (31)(32)(33). Our observations of anti-HIV-1 activity associated with 2=-C-methylcytidine are the first to be reported.…”
Section: Discussionmentioning
confidence: 99%